Measurements of Ice Crystal Fluxes from the Surface at a Mountain Top Site - Waldemar Schledewitz; Gary Lloyd; Keith Bower; Thomas Choularton; Michael Flynn; Martin Gallagher (Atmosphere, 2023)
New observations of anomalously high cloud ice crystal concentrations at the Jungfraujoch research station (Switzerland, 3.5 km a.s.l.) are presented. High-resolution measurements of these ice crystals using a high-speed 2D imaging cloud particle spectrometer confirm that the concentrations far exceed those expected from any known primary ice production mechanisms and are at temperatures well below those for known secondary ice production processes to contribute. The most likely explanation is due to a strong surface source generated by the interaction of turbulent deposition of supercooled droplets to fragile ice-covered snow surfaces. This process enhances the detachment of crystal fragments wherein the smaller size mode is turbulently re-suspended even at low wind speeds below expected blowing snow thresholds. These then continue to grow, adding significantly to the ice crystal number concentrations whose size and habit is determined by the transport time between the ice crystal source and measurement location and liquid water profile within the cloud. We confirm, using eddy covariance measurements of ice particle number fluxes, that the likely source is significantly far upwind to preclude flow distortion effects such that the source plume has homogenised by the time they are measured at the mountain top summit.